1991
DOI: 10.1007/bf01310496
|View full text |Cite
|
Sign up to set email alerts
|

Proviral sequences detected by polymerase chain reaction in peripheral blood cells of horses with equine infectious anemia lentivirus

Abstract: Proviral sequences in the peripheral blood mononuclear cells of 3 horses with acute equine infectious anemia virus were monitored using the polymerase chain reaction. Provirus was detected during the initial viremic episode in each horse and during each of 3 relapsing viremic cycles, although the appearance of provirus lagged behind the onset of viremia. Following each viremic episode, provirus levels in the peripheral monocytes decreased to less than 1 copy in 5 x 10(6) cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Most of this DNA is not integrated into host genomic DNA, but exists in linear and circular unintegrated forms (Rice et al, 1989). Provirus is also detectable in peripheral blood cells of acutely infected horses (Rice et al, 1989;O'Rourke et al, 1991).…”
Section: In Vivo Cell Tropismmentioning
confidence: 99%
“…Most of this DNA is not integrated into host genomic DNA, but exists in linear and circular unintegrated forms (Rice et al, 1989). Provirus is also detectable in peripheral blood cells of acutely infected horses (Rice et al, 1989;O'Rourke et al, 1991).…”
Section: In Vivo Cell Tropismmentioning
confidence: 99%
“…As the database on EIAV genes and antigens increases, 1,2,4,5,11,36,42 novel approaches to the delivery of accurate and practical diagnostic tests for EIA will emerge. If changes were to be made today, test kits should include determinants from several EIAV proteins and utilize a format that uses environmentally stable reagents and detection systems.…”
Section: Recommendations P26 Antibodies Are Detected In Confirmatory mentioning
confidence: 99%
“…The primary sites of EIAV replication in persistently infected horses has been examined by immunofluorescent techniques to detect viral antigens (23), by Southern blot analyses to detect proviral DNA (35), and more recently by qualitative PCR techniques to detect viral DNA or RNA (14,27,42). The results of these studies uniformly demonstrate that the high levels of viremia observed during acute EIA are associated with high levels of virus replication in macrophage-rich tissues, including liver, spleen, and kidney; peripheral blood mononuclear cells (PBMC) and other tissues appeared to contain only minor levels of virus infection, despite the high levels of virus in the blood.…”
mentioning
confidence: 99%